Quality assurance program and early toxicities in the phase III BONBIS randomized trial evaluating the role of a localized radiation boost in ductal carcinoma in situ. (November 2021) - Bourgier, Celine; Cowen, Didier; Castan, Florence; Lemanski, Claire; Gourgou, Sophie; Rivera, Sofia; Labib, Alain; Peignaux, Karine; Blanc-Onfroy, Magali Le; Benyoucef, Ahmed; Mege, Alice; Douadi-Gaci, Zineb; et al.
Highlights: The role of an additional boost to the tumor bed in DCIS is still unknown. Severity of acute skin toxicities is significantly increased by tumor bed boost. Smoking history and large breast CTV are predictive factors of acute toxicities. Dummy run before patients' inclusion reduced the risk of major TP deviations. Abstract: Purpose: To describe the quality assurance (QA) program and early toxicities in the phase III randomized trial BONBIS ( NCT00907868 ) on the role of a localized radiation boost in ductal carcinoma in situ (DCIS). Materials and methods: From November 2008 to July 2014, 2004 patients were randomized in arm A (only whole breast radiotherapy, WBRT) and arm B (WBRT + boost). The QA program involved 44 participant centers that performed the dummy run (DR). Compliance and uniformity of clinical target volume (CTV) delineations, and dose prescription and delivery according to the BONBIS trial radiotherapy guidelines were analyzed. Acute toxicities (during and up to 3 months after radiotherapy completion, NCI-CTCAE v3.0 classification) were evaluated in 1929 patients. Results: The differences in whole breast CTV (CTV1) and planning target volume (PTV1) were ≤10%, and the differences in boost CTV (CTV2) and PTV (PTV2) were ≥20% compared with the reference DR values; 95% of the prescribed dose encompassed 98.7% and 100% of the median CTV1 and CTV2. Grade ≥2 breast erythema (38.3% vs. 22.4% of grade 2 and 5.4% vs. 2.1% of grade 3, p  < 0.001), grade ≥2 dermatitis (2.8% vs. 0.7%, p  < 0.001), and grade 2 hyperpigmentation (6.9% vs. 3.6%, p  = 0.005) were more frequent in arm B than arm A. No acute lung or cardiac toxicity was observed. Smoking history, large breast size, and large breast CTV were strong predictive factors of grade ≥2 acute skin toxicities. Conclusions: The QA program showed deviations in breast and tumor bed delineation. The boost significantly increased acute skin toxicities.